To determine what value of \( c \) would make the second system of equations have the same solution as the first, we first need to analyze the first system of equations.
First System of Equations
- \( 4x + y = -1 \)
- \( x + y = 2 \)
We can solve for the variables \( x \) and \( y \).
From the second equation, we can express \( y \):
\[
y = 2 - x
\]
Now we can substitute \( y \) into the first equation:
\[
4x + (2 - x) = -1 \
4x + 2 - x = -1 \
3x + 2 = -1 \
3x = -1 - 2 \
3x = -3 \
x = -1
\]
Now substitute \( x = -1 \) back into \( y = 2 - x \):
\[
y = 2 - (-1) = 2 + 1 = 3
\]
So the solution to the first system is \( (x, y) = (-1, 3) \).
Second System of Equations
- \( 8x + 2y = -2 \)
- \( -4x + cy = -8 \)
Now, we check if the first equation of the second system is consistent with the solution obtained from the first system.
If we multiply the first equation of the first system by 2, we get:
\[
2(4x + y) = 2(-1) \
8x + 2y = -2
\]
So, the first equation of both systems is indeed the same.
Now, let's analyze the second equation of the second system:
To ensure the same solution happens for both systems, we can substitute \( x = -1 \) and \( y = 3 \) into the second equation and solve for \( c \):
\[
-4(-1) + c(3) = -8 \
4 + 3c = -8
\]
Now, subtract 4 from both sides:
\[
3c = -8 - 4 \
3c = -12
\]
Now, divide by 3:
\[
c = -4
\]
Thus, the value of \( c \) that will ensure both systems have the same solution is: